2018
DOI: 10.1080/09546634.2018.1468063
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-dye laser as an adjuvant treatment for discoid lupus erythematosus: a randomized, controlled trial

Abstract: Improvements of DLE can be achieved with PDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Yelamos et al found that using PDL in conjunction with hydroxychloroquine (which had not resolved the lesions as a monotherapy) in fact cured one child's cutaneous lupus on the dorsi of their hands with no recurrence at 2 years . Several other studies have also shown PDL to be effective both as an adjuvant therapy and monotherapy in cutaneous lupus.…”
Section: Sarcoid and Cutaneous Lupusmentioning
confidence: 99%
See 1 more Smart Citation
“…Yelamos et al found that using PDL in conjunction with hydroxychloroquine (which had not resolved the lesions as a monotherapy) in fact cured one child's cutaneous lupus on the dorsi of their hands with no recurrence at 2 years . Several other studies have also shown PDL to be effective both as an adjuvant therapy and monotherapy in cutaneous lupus.…”
Section: Sarcoid and Cutaneous Lupusmentioning
confidence: 99%
“…Rerknimitr et al carried out a double‐blind RCT in 48 discoid lupus lesions which were randomized to either receive 595‐nm PDL or no treatment 4 weekly for 4 months. Lesions treated with PDL improved and post‐PDL histology showed molecular changes found in disease remission pointing to the molecular effects of PDL on the disease . Al‐Niaimi et al found that individual telangiectasia in sarcoid can be safely and effectively treated with some improvement in lupus pernio and plaques with a vascular component …”
Section: Sarcoid and Cutaneous Lupusmentioning
confidence: 99%
“…Moreover, in a prospective study of 12 DLE patients with mild disease (baseline CLASI activity score 3-5), baseline CLASI activity significantly decreased after PDL, from a mean (SEM) of 4.4 ± 0.2 to 1.3 ± 0.3 after followup (p < 0.001) [120]. However, in a recent RCT involving 48 lesions in 9 DLE patients, no difference was seen in CLASI improvement with PDL as compared with the control [121].…”
Section: Pulsed Dye Laser (Pdl)mentioning
confidence: 92%
“…At each visit, a number of objective measurements were carried out including erythema index, measured by DSMII ColorMeter (Cortex technology, Hadsund, Denmark) and papulopustular lesion count. In addition, clinical photographs were taken by Visia (Canfield, NJ) and the photographs were evaluated at the end of the study by three independent dermatologists to obtain a physician global assessment (PGA) score . The score is a quartile ordinal grading scale used to compare the clinical findings before and after the treatment, so a score of one means an improvement of 25% and a score of ‐1 means a worsening of 25%, and changes move from 0 (no change) at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Pulsed‐dye laser (PDL) has been reported to provide better outcomes for inflammatory dermatoses, namely acne, discoid lupus erythematosus and nail psoriasis . Typically, PDL, with wavelengths of 585 and 595 nm, is used to treat vascular lesions.…”
Section: Introductionmentioning
confidence: 99%